Análisis del efecto de la impregnación de cloruro de calcio con deshidratación osmótica por vacío en rebanadas de pimientos para conservas - Grijalva Gomez, Omar (2009)
This paper presents the comparative study of the influence of packing in the shelf-life of tilapia fillets stored at refrigerator temperatures. The objective is to develop a package capable of improving the organoleptic characteristics such as shelf-life of the product. To develop this study we chose to use in modified atmosphere packaging of filleted. For this we used different concentrations in each mixture. The final product was subjected to two tests, the first microbiological and sensory evaluation at the second, which established the difference between the sensory characteristics and packaging. Finally presents the proposal package which has better influence on the product packaging to the given conditions. The end product is a package that helps increase the shelf life as well as the organoleptic properties of choice for this type of product.